Leucocytes, urea and glucose levels in Albino Wistar rats exposed to doses of isolated Achatina achatina snail lectin - Odiegwu, Chukwujekwu Nwabueze C.; Chianella, Iva; Odiegwu, U. O.; Okolie, U. V.; Ifejirika, E. C. (Magna Scientia Publication, 2021)
There are five (5) types of mature White blood cells (WBC) or Leucocytes found in the peripheral blood viz, Neutrophils (NEU), Eosinophils (EOS) and Basophils (BAS) (granulocytes); Monocytes (MON) and Lymphocytes (LYM) (agranulocytes). Urea is an organic chemical compound, and is essentially the waste produced by the body after metabolizing protein. Urea levels can be used to detect diseases and disorders that affect the kidneys. A common disease related to irregular management of glucose is diabetes. Lectins are proteins that recognize specifically and bind reversibly the carbohydrate-containing molecules of foreign cells and that elicit diverse physiological responses in various organisms. A total of 120 samples of Nigeria Achatina achatina snail specie were collected, authenticated at the Zoology Department of University of Nigeria, Nsukka and 80mls of pooled crude Lectin extract was obtained. Purifications were performed on 20mls of the crude extract in three steps viz, Ammonium sulphate precipitation and Dialysis (Partial purifications), Con A Sepharose 4B affinity Chromatography column (Complete purification). The affinity purified Lectin was used for all the tests conducted in this research. The crude, partially and complete/affinity purified Lectin extracts were subjected to Haemagglutination tests. The Lectin was further assessed to determine its effects on Leucocytes, Urea and Glucose as follows: A total of Thirty-five (35) male Albino Wistar Rats weighing 101-180g and aged 2-3 months obtained from the Animal house of University of Nigeria, Nsukka, were used in this research. The animals were Grouped into 5 (A-E) and allowed for 2 weeks acclimatization. Graded doses of 0.04ml, 0.05ml and 0.06ml of the Affinity purified Lectin were injected intra-peritoneally into each of the Rats in Groups A-D (test groups) according to their body weights at intervals of 2 days for 1 week. Group E served as the control. Two (2) mls of blood was collected from each of the Rats before and 24 hours after the last day of Lectin Doses injections for the following tests: WBC-Total and Differential counts (using Sysmex Corporation, 1999 automated equipment), Urea and Glucose estimations (performed by means of Urease-Berthelot and GOD-PAP Randox Monza automated analyser methods respectively). The results of the research showed as follows: On complete/affinity purification, 15mls of pure sample containing only the high molecular weight Lectin was obtained. The haemagglutination tests conducted showed on standardization preferential agglutination with Blood group A type. Bar Charts statistics show that there was Post Lectin Doses injections mean increase in Total WBC, NEU, LYM and decrease in MON, EOS, BAS, Urea and Glucose levels. However, the differences in Pre and Post Lectin Doses injections mean values of these parameters were further subjected to One way analysis of variance (ANOVA) test statistics to determine if statistically significant. The ANOVA statistics show that the effects of the Lectin on all the assessed Leucocytes parameters viz, Total WBC, and Differential LYM, NEU, MON, EOS, BAS, the Urea and Glucose levels were found to be statistically insignificant. However, the EOS values of only group A was statistically significant. This research has therefore succeeded in Assessment of Activities of the A. achatina snail Lectin on Leucocytes, Glucose and Urea levels.
Keywords: Achatina achatina; Snail Lectin; Effects on Leucocytes; Glucose; Urea